Pengaruh Kinerja Manajemen UMKM di Kota Padang terhadap Penerapan Laporan Keuangan Berbasis SAK EMKM - Andre Bustari; D Desmiwerita (Journal of Economics and Management Scienties, 2023)
Accounting practices, financial statements produced by an entity, especially in SMEs in Padang that the financial statements have been stated in accordance with accounting standards based on SAK EMKM. SAK EMKM is applied to SMEs in Indonesia for the preparation of effective financial statements as of January 1, 2018. Lack of understanding of Financial Accounting Standards (GAAP) from owners and managers due to the absence of regulations that require the preparation of financial statements for SMEs. The main problem in this research is how the influence of small and medium business perceptions on the use of SAK EMKM. The purpose of this study was to determine the effect of the performance of SME management in Padang on the application of financial statements based on SAK EMKM. The results showed that the performance of SME management in Padang had a significant effect on the application of financial statements based on SAK EMKM. The contribution of the performance of SME management in Padang has a significant effect on the application of financial statements based on SAK EMKM is 41.1% while the remaining 58.9% is influenced by other factors beyond this research